Fibrous dysplasia of the skull: neurological manifestations - Paulo Eduardo Freitas; Telmo Ramos Ribeiro; Mario Ferreira Coutinho; Adão Anicet (Arquivos de Neuro-Psiquiatria)
The neurological manifestations of eight patients with osseous fibrous dysplasia of skull were retrospectively studied. In this series, the frontal bone was involved in 75% of the patients, the sphenoid or temporal bones in 37.5%, and the parietal in 25%. It was observed that cranial deformities occurred in all but one case, headache was present in 87.5% of the patients, visual disturbances in 50%, proptosis in 25%, and auditive symptoms in 12.5%. Six out of the eight patients were operated on: three of the four who presented progressive visual loss had postoperative improvement. In their follow up, none presented, until now, evidence of recurrence or worsening of symptoms, confirming the benign nature of fibrous dysplasia.